2002
DOI: 10.1074/jbc.m205564200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Membrane Protein, Ros3p, Is Required for Phospholipid Translocation across the Plasma Membrane inSaccharomyces cerevisiae

Abstract: Ro09-0198 (Ro) is a tetracyclic peptide antibiotic that binds specifically to phosphatidylethanolamine (PE) and causes cytolysis. To investigate the molecular basis of transbilayer movement of PE in biological membranes, we have isolated a series of budding yeast mutants that are hypersensitive to the Ro peptide. One of the most sensitive mutants, designated ros3 (Ro-sensitive 3), showed no significant change in the cellular phospholipid composition or in the sensitivity to amphotericin B, a sterol-binding pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(184 citation statements)
references
References 54 publications
7
175
2
Order By: Relevance
“…lem3 and dnf1∆ dnf2∆ mutants, but not the dnf1∆ or dnf2∆ single mutant, are hypersensitive to cinnamycin [10,14], consistent with the defects in NBD-PE internalization in these mutants.…”
Section: The Lem3(r316w) Mutation Does Not Impair the Putative Aplt Asupporting
confidence: 60%
See 4 more Smart Citations
“…lem3 and dnf1∆ dnf2∆ mutants, but not the dnf1∆ or dnf2∆ single mutant, are hypersensitive to cinnamycin [10,14], consistent with the defects in NBD-PE internalization in these mutants.…”
Section: The Lem3(r316w) Mutation Does Not Impair the Putative Aplt Asupporting
confidence: 60%
“…Unexpectedly, Lem3p(R316W) also coimmunoprecipitated with Dnf2p-13Myc, suggesting that the Lem3p(R316W)-Dnf2p complex is formed in the ER, but is not transported out of the ER due to the action of the ER qual-ity control mechanism. Kato et al showed that Lem3p/Ros3p was associated with the detergent-insoluble fraction [14]. As shown in Fig.…”
Section: Isolation Of Lem3 Mutations That Affect the Growth Of The CDmentioning
confidence: 86%
See 3 more Smart Citations